2021
DOI: 10.3390/ijms22083873
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Anti-Tumoral Potential of CD-NHF by Modulating PI3K/Akt Axis in U87 Ex Vivo Glioma Model

Abstract: Background: In the latest years, there has been an increased interest in nanomaterials that may provide promising novel approaches to disease diagnostics and therapeutics. Our previous results demonstrated that Carbon-dots prepared from N-hydroxyphthalimide (CD-NHF) exhibited anti-tumoral activity on several cancer cell lines such as MDA-MB-231, A375, A549, and RPMI8226, while U87 glioma tumor cells were unaffected. Gliomas represent one of the most common types of human primary brain tumors and are responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The in vitro investigations showed that the level of IL-6 mRNA in cancer cells treated with Mn-doped CDs-NHF was significantly lower than that in the control cells (which were treated with Gadovist, a gadolinium-based contrast agent). Luta et al [ 381 ] found a significant impairment in the IL-6 level in all of their groups treated with CDs-NHF thus confirming the antitumoral properties of these CDs.…”
Section: Sustained Aberrant Angiogenesismentioning
confidence: 80%
“…The in vitro investigations showed that the level of IL-6 mRNA in cancer cells treated with Mn-doped CDs-NHF was significantly lower than that in the control cells (which were treated with Gadovist, a gadolinium-based contrast agent). Luta et al [ 381 ] found a significant impairment in the IL-6 level in all of their groups treated with CDs-NHF thus confirming the antitumoral properties of these CDs.…”
Section: Sustained Aberrant Angiogenesismentioning
confidence: 80%
“…Since the widely used contrast agent, gadolinium, presents various side effects, we aimed to develop theranostic agents by doping CDs-NHF with ions that present lower toxicity. Previously, we have demonstrated the anti-tumoral properties of non-doped CDs-NHF in various models [ 15 , 16 , 42 ]. In our new experimental investigations, we decide to combine the anti-tumoral properties of CDs-NHF with MRI imaging capabilities of Gd 3+ , Fe 3+ , or Mn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated in vitro and in vivo the anti-tumoral properties of N-Hydroxyphthalimide-derived Carbon Dots (CDs-NHF) in a breast cancer model [ 15 ]. In another paper, we have shown that although CDs-NHF alone do not impair U87 glioblastoma cell line viability, combining lower doses of key pathways inhibitors with lower CDs-NHF doses significantly reduced cell viability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%